Thematic Learning Based on Critical Thinking Skills using Blended Learning System in Elementary School - Triyanto, Joko; Sukarno, Sukarno; Kurniawan, Sandra Bayu (Universitas Pendidikan Ganesha, 2022)
Learning during a pandemic requires innovation so that learning runs well and can develop students' critical thinking skills. One of the learning innovations is applying a blended learning system in thematic learning. This study aimed to analyze the planning, implementation, and thematic learning outcomes based on critical thinking skills using a blended learning system for fifth-grade students in elementary schools. This type of research is descriptive qualitative using a case study approach with a subject of 37 fifth grade elementary school students. Data collection techniques in this study through direct observation, interviews, and documentation in the form of data related to research to strengthen the information. The data that has been collected is then grouped and validated by source triangulation and triangulation techniques. The data is analyzed by data reduction, data presentation, and conclusion drawing. The results of this study are 1) Planning of thematic learning based on critical thinking skills with a BLS begins with the preparation of curriculum documentation, socialization, then IHT (In House Training) activities, and the preparation of syllabus and Learning Implementation Plans (RPP) thematic based on critical thinking skills. 2) Implementation of thematic learning based on critical thinking skills with a blended learning system combining face-to-face learning and online learning that can accommodate students' critical thinking skills through a series of applied learning activities. 3) The results of thematic learning based on critical thinking skills obtained a good category which includes an assessment of cognitive, affective, and psychomotor aspects.